Influence of Thermal-mechanical Coupling of Single Particle on Grinding Surface Roughness - Hu, Lai; Wang, Zixi; Wang, Yuming (Manufacturing Technology Journal, 2024)
Grinding is one of the most important processes in machining precision rotating parts. GF & GT (grinding force and grinding temperature) of single particle in grinding wheel have great influence on surface roughness. This study established the GF & GT models of single particles. Abaqus was used to analyze the coupling between GF & GT of single particle. Combined with grinding parameters (grinding depth and grinding speed), the influence of GF & GT on the range of surface roughness of single particle abrasive was comprehensively studied. The machining and experimental analysis of precision aerospace bearings were carried out through theoretical analysis. The results show that with the increase of grinding depth, the GF & GT in X and Z directions increase gradually. However, the grinding temperature does not increase linearly with the increase of grinding depth. Compared with the grinding speed, the influence of grinding depth on the grinding force in Y and Z directions is much greater than that in X, which is 7.38 times and 5.81 times of the grinding speed, respectively. Grinding depth has the greatest influence on surface roughness, which is 3.6 times the grinding speed. When the test speed is constant at60000 rev/min, the bearing temperature is between 30 °C and 65 °C and most of them are within 44 °C. The test data meet the requirements, and all indexes are controllable. The above conclusions provide a theoretical basis and selection of process optimization parameters for grinding precision rotating parts.
Keywords: GF ＆ GT; Surface roughness; Single particle; Range analysis